Influence of the Nursing Practice Environment on Job Satisfaction and Turnover Intention - Sang-Yi Lee; Chul-Woung Kim; Jeong-Hee Kang; Tae-Ho Yoon; Cheoul Sin Kim (Korean Society for Preventive Medicine, 2014)
Objectives: To examine whether the nursing practice environment at the hospital-level affects the job satisfaction and turnover intention of hospital nurses. Methods: Among the 11 731 nurses who participated in the Korea Health and Medical Workers' Union's educational program, 5654 responded to our survey. Data from 3096 nurses working in 185 general inpatient wards at 60 hospitals were analyzed using multilevel logistic regression modeling. Results: Having a standardized nursing process (odds ratio [OR], 4.21; p<0.001), adequate nurse staffing (OR, 4.21; p<0.01), and good doctor-nurse relationship (OR, 4.15; p<0.01), which are hospital-level variables based on the Korean General Inpatients Unit Nursing Work Index (KGU-NWI), were significantly related to nurses' job satisfaction. However, no hospital-level variable from the KGU-NWI was significantly related to nurses' turnover intention. Conclusions: Favorable nursing practice environments are associated with job satisfaction among nurses. In particular, having a standardized nursing process, adequate nurse staffing, and good doctor-nurse relationship were found to positively influence nurses' job satisfaction. However, the nursing practice environment was not related to nurses' turnover intention.